Clinical Characteristics of 195 Cases of COVID-19 with Gastrointestinal Symptoms COVID-19 with Gastrointestinal Symptoms - Zhan, Ting; Tang, Yalin; Han, Zheng; Zhu, Qingxi; Tan, Jie; Liu, Meng; Cai, Yisan; Huang, Min; Chen, Xiaoli; Cheng, Xueting; et al. (Turkish Journal of Gastroenterology, 2021)
Background: Patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), have fever, dry cough, dyspnea, and fatigue. The disease has now become a global pandemic. The purpose of this study was to explore the relationship between COVID-19 and gastrointestinal (GI) symptoms. Methods: We collected and analyzed data on patients with laboratory-confirmed COVID-19 by high-throughput sequencing or reverse transcription-polymerase chain reaction. We reviewed electronic medical records of 405 hospitalized COVID-19 patients in the Third Hospital of Wuhan. Results: Among the 405 confirmed patients, 210 had no GI symptoms, 195 had GI symptoms, and the first symptom of 155 patients was GI. The prevalence of vascular and digestive diseases in the group with GI symptoms was significantly higher than in the group without GI symptoms. In patients with GI symptoms, the proportion with fever, cough, dysphoria, chest tightness, poor appetite, chest pain, and pharyngeal pain was significantly higher than in those without GI symptoms. There was no significant difference in imaging between the 2 groups. In patients with GI symptoms, the proportion with increased procalcitonin (PCT) level and decreased lymphocyte count was significantly higher than in those without GI symptoms. Conclusion: COVID-19 patients with GI symptoms had significantly more vascular and digestive system diseases and were more likely to have clinical manifestations of fever, cough, poor appetite, chest tightness, chest pain, insomnia, and pharyngeal pain. There were more patients with diarrhea, nausea, and vomiting. Patients with GI symptoms were more likely to have increased PCT and decreased lymphocyte count.